Sensitivity and specificity test of fine needle aspiration biopsy in determining thyroid nodule diagnosis - Teguh Aryandono, Ahmad Aryono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Based on guideline of the American Association of Clinical Endocrinologist, fine needle aspiration (FNA) is believedas effective method to differentiate between benign and malignant thyroid nodule. At Dr. Sardjito Hospital,during2004 â 2008 there were 12 cases of false negative from 14 cases of thyroid malignancy. The high false negativevalue raised question about the role of FNA in determining thyroid nodule diagnosis. The purpose of this study is tofind out sensitivity and specificity of FNA in determining thyroid nodule diagnosis at Dr. Sardjito Hospital Yogyakarta.Patients underwent FNA and surgery for thyroid nodule were collected between January 2004 until December2008. The result of FNAwas compared to histopathological result then sensitivity and specificity test were performedrespectively. The fine needle aspiration was conducted to 120 patients. It consist of 23 men and 97 women, mostly41 â 50 years old. The results of FNA were four of malignancy, 74 of benign, and 42 of follicular neoplasm.Histopathological result showed malignant in 23 patients and benign in 97 patients. The FNA at Dr. Sardjito Hospitalshowed 14.29%of sensitivity, 96.86%of specificity, 50%of PPV, 83.78% of NPV, 4.55 of LR +0.884 of LR-,18.92% of prevalence, and 86.49% of accuracy. The thyroid FNA at Dr. Sardjito Hospital showed low value ofsensitivity and high value of specificity. Futhermore, the thyroid FNA showed minimal role in determining thyroidnodule diagnosis.Keywords : thyroid nodule-diagnosis-fine needle aspiration-sensitivity-specificity